DCI Banks. Season four [videorecording (DVD)] - Tompkinson, Stephen, 1965-; Lowe, Andrea, 1975-; Catz, Caroline; Robinson, Peter, 1950- (BBC Worldwide, 2015)
Stephen Tompkinson returns as Detective Chief Inspector Alan Banks in three more gripping crime stories.